The Pengaruh Indikator Rasio Keuangan Terhadap Non-Performing Financing Net Pada PT Bank Syariah Indonesia Tbk - Husni Mubarok (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The study aims to analyze the Effect of Financial Ratio Indicators on Non-Performing Finance Net at PT Bank Syariah Indonesia Tbk 2009-2021. The research created a quantitative case study descriptive model that resulted in a partial test of the ROA variable showing the most powerful influence on the hypothesis that Ho accepted the residuals were normally distributed to the NPF Net, while the simultaneous test was carried out together with indicators of the independent variable the level of correlation was very strong. The dependent variable hypothesis was accepted that the residual was normally distributed to NPF Net.